Addressing the financial consequences of cancer: qualitative evaluation of a welfare rights advice service. - Suzanne Moffatt; Emma Noble; Martin White (PLoS ONE)
Background The onset, treatment and trajectory of cancer is associated with financial stress among patients across a range of health and welfare systems and has been identified as a significant unmet need. Welfare rights advice can be delivered effectively in healthcare settings, has the potential to alleviate financial stress, but has not yet been evaluated. We present an evaluation of a welfare rights advice intervention designed to address the financial consequences of cancer. Methods Descriptive study of welfare outcomes among 533 male and 641 female cancer patients and carers aged 4-95 (mean 62) years, who accessed the welfare rights advice service in North East England between April 2009 and March 2010; and qualitative interview study of a maximum variation sample of 35 patients and 9 carers. Results Over two thirds of cancer patients and carers came from areas of high socio-economic deprivation. Welfare benefit claims were successful for 96% of claims made and resulted in a median increase in weekly income of £70.30 ($109.74, €84.44). Thirty-four different types of benefits or grants were awarded. Additional resources were perceived to lessen the impact of lost earnings, help offset costs associated with cancer, reduce stress and anxiety and increase ability to maintain independence and capacity to engage in daily activities, all of which were perceived to impact positively on well-being and quality of life. Key barriers to accessing benefit entitlements were knowledge, system complexity, eligibility concerns and assumptions that health professionals would alert patients to entitlements. Conclusions The intervention proved feasible, effectively increased income for cancer patients and was highly valued. Addressing the financial sequelae of cancer can have positive social and psychological consequences that could significantly enhance effective clinical management and suitable services should be routinely available. Further research is needed to evaluate health outcomes definitely and assess cost-effectiveness.